Exergoeconomic Study of a Combined Flash-Binary Cycle at Dieng Unit 2 Geothermal Power Plant - Theophilus, Jason
Indonesia has vast potential of geothermal energy. In order to meet future electricity demands, PLN has plans to increase the provision of geothermal power plants. Past research has shown that a combined flash-binary cycle geothermal power plant is proven to increase the thermodynamic performance parameters for a given geothermal resource. Exergoeconomics is a branch of engineering which combines thermodynamic aspects and economic aspects in a single approach. Previous research has shown that the result from exergoeconomic optimization is different than the result from thermodynamic optimization. This study is done by first specifying the design variables of a geothermal combined flash-binary cycle power plant, and then reviewing the thermodynamics and thermoeconomics performance. The design variables chosen are the separator pressure and the Organic Rankine Cycle (ORC) pump head. The performance parameters reviewed are the exergy efficiency and the average levelized cost per unit of exergy of the product (electricity). This study is done on Dieng Unit 2 Geothermal Power Plant, which is still in the feasibility study phase, and used as the basis for well fluid properties and the recommended constraints. Based on the simulation results, there is an optimal decision variable for both performance parameters at 3150 kPa pump head and 2500 kPa separator pressure. On that point, the exergy efficiency reaches 52,38%, and the electricity cost per unit exergy is 3,04x10 9 USD/J. Both performance parameters reach optimum values on the same point, which shows that there is no difference between thermodynamic and exergoeconomic optimization results. On the single-flash cycle simulation result, the performance parameters reach optimal values at 1900 kPa separator pressure. The cost of electricity per unit exergy is 4,27x109 USD/J and the exergy efficiency is 36%. It can be concluded that the use of the flash-binary cycle will be good for both performance parameters.